Understanding the Structural Complexity of Induced Travel Demand in Decision-Making: A System Dynamics Approach - Angarita-Zapata Juan S. (Organizacija, 2016)
Background and purpose: Induced travel demand (ITD) is a phenomenon where road construction increases vehicles’ kilometers traveled. It has been approached with econometric models that use elasticities as measure to estimate how much travel demand can be induced by new roads. However, there is a lack of “white-box” models with causal hypotheses that explain the structural complexity underlying this phenomenon. We propose a system dynamics model based on a feedback mechanism to explain structurally ITD.